2017
DOI: 10.21608/jva.2017.45444
|View full text |Cite
|
Sign up to set email alerts
|

Significant Diseases of Two Very Aged Red Foxes (Vulpes vulpes, Demarest 1820)

Abstract: Diseases of two very old red foxes Lawler et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The authors observed that varying bone quality may result from disease severity, rate of progression, and interspecies differences. In another report, chronic renal disease in elderly sheltered red foxes (Lawler et al, 2017) did not occur with overt NSH. These studies further underscore the importance of focused attention on differential diagnosis, and understanding that outcomes of diseases may be variable and time related.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The authors observed that varying bone quality may result from disease severity, rate of progression, and interspecies differences. In another report, chronic renal disease in elderly sheltered red foxes (Lawler et al, 2017) did not occur with overt NSH. These studies further underscore the importance of focused attention on differential diagnosis, and understanding that outcomes of diseases may be variable and time related.…”
Section: Discussionmentioning
confidence: 86%
“…Skeletal components that were available from each of the foxes are shown in Supporting Information S1. Skeletal observations were divided into categories: pathology that is unique to the circumstances of these five foxes (Conlogue et al, 1979; Kucklick et al, 2002; Ogden & Conlogue, 1981; Spraker & White, 2017; Whalen et al, 1977) and pathology that can be observed on skeletal components of many foxes and other canids (Lawler, Becker, et al, 2016; Lawler & Evans, 2016; Lawler et al, 2012, 2017, 2019; Mustonen et al, 2017) (Table 1). The volume and detail of both observation categories necessitate presentation as a Supporting Information S2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations